Discourse analysis of the perception of the Chinese initiative «One Belt, One Road» in Central Asian countries (Хабаршы. Психология және социология сериясы, 2021)
The initiative «One belt, one road» becomes increasingly recognized among the population of Cen- tral Asian countries year by year. The information environment is also relevant to this topic. Nowadays you can find more articles with headlines «China increases investment in Central Asia», «China builds a new factory in Uzbekistan or Kazakhstan», «China increases exports through Central Asia», etc. As China’s attitude towards the countries of Central Asia is growing, so is the information space. China’s attitude towards the countries of Central Asia is growing. The development of modern technology and social media allows many independent media to present today’s realities. Thus, by analyzing the dis- course of the information space of these countries, one can see how China and the Chinese BRI initiative are perceived in society. The aim of the study is therefore to analyse the Kazakh, Kyrgyz and Uzbek discourse on Chinese investment and the Chinese BRI initiative. The significance of this study is that very few papers address the social perception of the BRI initiative. Most of the works describe more the economic, political or logistical peculiarities of the project. An analysis of Kazakh, Kyrgyz and Uzbek media was chosen as the research method. During the research, 117 articles were analysed in Russian, Kazakh, Kyrgyz and Uzbek. The article was searched on different news sites, according to keywords:«China», «BRI», «Chinese investment» and «Chinese projects». The study is also descriptive and is based on the context of China’s perception of the Chinese BRI initiative. The results of the study showed that the discourse in these countries is very diverse and has both similarities and differences. The importance of the study lies in the fact that there are not many comparative studies on the topic at this time, as many authors consider one country as a case.Key words: initiative «one belt, one road», Silk Road, Central Asia, China, perception.